Optimization of Two–Mass Electromechanical System - Karaliūnas, B. (Elektronika ir Elektrotechnika, 2010)
The issues of two – mass electromechanical optimization are analyzed. The probable methods of optimization and measures were discussed. The structural diagram of system optimization is presented, it is comprised of DC motor with two – mass mechanical link Matlab/Simulink model, PID regulator and units of signal limitations. The optimization process is finalized, when the characteristics of transitional process corresponding the proposed parameters are derived. The results obtained indicate that after determining the optimal values of the amplifying coefficients for the regulator during the optimization it is possible significantly reduce the oscillations of drive velocity, acceleration, current and torque and obtain optimal dynamic characteristics.